Sequential algorithm of parabolic equation in solving thermal control process on printed circuit board - A. Ghaffar, Zarith Safiza; Alias, Norma; Ismail, Fatimah Sham; Muhamed Murid, Ali Hassan; Hassan, Hazrina (Ibnu Sina Institute for Fundamental Science Studies, 2008)
This paper focuses on the implementation of sequential algorithms for the simulation of parabolic equation in solving the thermal control systems. The platform of the temperature behaviour prediction is based on printed circuit board. The numerical finite-difference method (FDM) is used to design the discretization of these partial differential equations. The results of finite-difference approximation are presented graphically. Numerical methods that are used in solving the problem are the method of Jacobi, Gauss-Seidel, Red-Black Gauss-Seidel, Successive Over Relaxation (SOR) and Red-Black Successive Over Relaxation. The numerical analysis is treated done in terms of time execution, computation complexity, number of iterations, accuracy and convergence rate